April Storm : a Novel - Meacham, Leila 1938-2021 (New York, NY : Harper, 2024)
"A much-anticipated posthumous novel from the beloved author of Roses and Dragonfly, April Storm follows a suburban housewife who discovers she's being tracked by a private detective-and a murderer"--
Keywords: Detective and mystery fiction; Novels